Development of human pose models for sports dynamics analysis using video image processing techniques - Kannan, P.; Ramakrishnan, R. (International Journal of Sports Science and Engineering, 2012)
Monitoring and detection of human body movements is a very interesting and important research problem in the video based applications. It has gained more importance in the field of computer vision due to its potential applications such as sports, video surveillance, security systems, home care and patient monitoring systems. A thinning algorithm is proposed to find the skeleton of the sports person. The development of human pose modeling plays an important role in the sport analysis. The pose models are constructed using the feature points on the human body. Eleven feature points are tracked and identified from the sports person to construct two dimensional body modeling for analyzing sports dynamics.